2007
DOI: 10.1007/s10597-007-9082-y
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health of Rural Young Adults: Prevalence of Psychiatric Disorders, Comorbidity, and Service Utilization

Abstract: Few studies estimate rural psychiatric disorder rates. No study has reported either DSM-III-R or DSM IV disorder prevalence and mental health service use among US rural young adults. This paper reports psychiatric disorder prevalence, comorbidity, service utilization, and disorder correlates in a community sample of 536 young adults, aged 19 to 23 years, living in the rural Midwestern US. More than 60% of the sample met criteria for a lifetime disorder. Substance use disorders were most prevalent. Results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 58 publications
1
20
1
Order By: Relevance
“…Results showed that low-SES rural students, especially females, had more mental health problems than high-SES rural students, who in turn had more mental health problems than students in urban schools. Our results are in clear contrast with those from studies conducted in the United States (Rueter et al, 2007), which found no significant urban-rural differences in adolescents' mental health. One explanation of this inconsistency is that in industrialized societies like the United States, urban-rural differences in economic Step 1 Step 2 Step 3 Step 4 Urban-Rural Differences in Chinese Adolescents' Mental Health development are not as dramatic as those in developing countries such as China.…”
Section: Discussioncontrasting
confidence: 99%
“…Results showed that low-SES rural students, especially females, had more mental health problems than high-SES rural students, who in turn had more mental health problems than students in urban schools. Our results are in clear contrast with those from studies conducted in the United States (Rueter et al, 2007), which found no significant urban-rural differences in adolescents' mental health. One explanation of this inconsistency is that in industrialized societies like the United States, urban-rural differences in economic Step 1 Step 2 Step 3 Step 4 Urban-Rural Differences in Chinese Adolescents' Mental Health development are not as dramatic as those in developing countries such as China.…”
Section: Discussioncontrasting
confidence: 99%
“…One study using a North Carolina population reported major depressive disorders as being twice as frequent in urban areas [17], with another study focusing on Mexican-Americans in California also reporting a higher prevalence of any psychiatric disorder in urban areas [15]. In contrast, a study evaluating cancer survivors found more symptoms of anxiety and depression among rural populations [16], and a study done in the Midwest found substance use disorders more prevalent among rural residents [18]. Another study found the prevalence of psychiatric disorders in rural primary care offices to be as high as those in urban offices [19].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Costello, Keeler, and Angold (2001) found roughly equivalent prevalence rates for children aged 9 to 11 living in four poor rural counties in North Carolina when compared to national prevalence rates. Another study found that young adults in the rural Midwest had rates of mental health disorders comparable to or higher than certain urban communities (Rueter, Holm, Burzette, Kim, & Conger, 2007). …”
Section: Introductionmentioning
confidence: 99%